2023
DOI: 10.1186/s13287-023-03273-z
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells conditioned medium exerts anti-tumor effects on KGN cells in a cell density-dependent manner through activation of the Hippo pathway

Abstract: Background The conditioned medium from human umbilical cord mesenchymal stem cells (UCMSCs-CM) provides a new cell-free therapy for tumors due to its unique secretome. However, there are many contradictory reports about the effect of UCMSCs-CM on tumor cells. The loss of contact inhibition is a common characteristic of tumor cells. A relationship between the effect of UCMSCs-CM on tumor cells and contact inhibition in tumor cells is rarely concerned. Whether the effect of UCMSCs-CM on tumor cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the small molecule inhibitor XMU-MP-1 selectively inhibits the activity of Hippo kinases MST1 and MST2 and upstream of LATS1/2 and, subsequently, enables YAP nuclear activity ( 34 , 35 ). We used this drug to investigate the effect of activating endogenous YAP on ccRCC cell phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the small molecule inhibitor XMU-MP-1 selectively inhibits the activity of Hippo kinases MST1 and MST2 and upstream of LATS1/2 and, subsequently, enables YAP nuclear activity ( 34 , 35 ). We used this drug to investigate the effect of activating endogenous YAP on ccRCC cell phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…These newly formed blood vessels may support the delivery of oxygen and nutrients to the surrounding tissues, reducing hypoxia and preventing IH formation [ 20 ]. Another possible mechanism is that UC-MSCs have immunomodulatory properties [ 21 ] which are important factors in IH development by modulating the immune response and can suppress inflammation in the vessel wall [ 22 ]. This anti-inflammatory effect may prevent the activation of smooth muscle cells and the subsequent proliferation of these cells, which is a key process in IH development [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, umbilical cord mesenchymal stem cells have been found to possess immunomodulatory properties. These cells can modulate the immune response and reduce inflammation, which are important factors in intimal hyperplasia development, 17 and it may promote vascular repair and inhibit the development of intimal hyperplasia. 18 The combination of umbilical cord mesenchymal stem cells and HIF-1α can enhance these angiogenic properties and improve the outcomes of arteriovenous fistula creation.…”
Section: Level Of Hif-1αmentioning
confidence: 99%